Research on pragmatic impairment in autistic children during the past two decades (2001–2022): hot spots and frontiers—based on CiteSpace bibliometric analysis - Liu, Yanqin; Tian, Xin; Mao, Haoran; Cheng, Lulu; Wang, Peng; Gao, Yang (Frontiers in Psychology, 2024)
Pragmatic impairment has become a critical aspect of language development in autistic children and has gained significant academic attention over the past two decades. This study leverages bibliometric methods to conduct an exhaustive analysis of literature derived from Web of Science database. Utilizing CiteSpace software, we construct a knowledge map to dissect the academic hotspots in research related to pragmatic impairment in autistic children. This enables us to delineate the evolutionary trajectory of this research domain, analyze the prevailing research dimensions, and anticipate potential future dimensions. Our findings indicate that research hotspots in this field over the past two decades predominantly concentrate on assessing and diagnosing pragmatic impairment in autistic children, intervention strategies, and theory of mind. The research scope on pragmatic impairment in autistic children has progressively broadened and deepened. Research has evolved from initial descriptions and interpretations of autism to exploring the theory of mind in high-functioning, school-aged children. The current emphasis is on examining the specific skills that these children possess.